Influência da compactação no colapso de um solo arenoso - Castro, Ana Patrícia Aranha [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Soil compaction is an essential activity in geotechnical works and its proper execution is able to promote significant improvements in soil behavior. Thus, the knowledge of the soil and the control of implementation methods are indispensable for the good performance in work. Variation of soil moisture and, consequently, in soil suction field directly influences their behavior when submitted or not to overloads. The compaction field control is the most viable alternative for improving collapsible soils. Poorly compacted landfill soils can have collapsible behavior when flooded. In this sense, this research is a study of compaction as improvement method for a sandy collapsible soil from the region of Bauru-SP. Characterization tests, Proctor Normal compaction, as well as conventional oedometric tests and controlled suction oedometric tests are part of the research experimental program. From the results obtained, it was found that the collapse settlements increase with lower degree of compaction. The initial soil moisture before the flood also influences the magnitude of soil collapse. Soils with low initial moisture content have greater collapse when they are wet. For the studied soil, collapse settlements are small and almost negligible for soil with degree of compacted of 90%. Tests performed on samples compacted under the same conditions of natural soil compactness demonstrated that the soil deformability is affected by its low density and the collapse can be higher than the ones obtained in the same soil in natural condition. At this work, a more practical representation of the relationship of collapse potential with soil compaction curve is proposed. Thus, it was found that compaction can sufficiently reduce the problems arising from soil collapsibility with some control in process.

A compactação dos solos é uma atividade fundamental nas obras geotécnicas e sua correta execução é capaz de promover melhorias significativas no comportamento do solo. Desse modo, o conhecimento acerca do solo e o controle dos métodos de execução são indispensáveis para o bom desempenho de uma obra. A variação da umidade do solo e, consequentemente, da sucção em campo influencia diretamente no seu comportamento quando submetido ou não a sobrecargas. O controle da compactação em campo representa a alternativa mais viável para melhoria de solos colapsíveis. Solos de aterros mal compactados podem apresentar comportamento colapsível quando inundados. Nesse contexto, esta pesquisa trata de um estudo acerca da compactação como método de melhoria de um solo colapsível arenoso proveniente da região de Bauru-SP. Ensaios de caracterização, de compactação Proctor Normal, assim como ensaios edométricos convencionais e com controle de sucção compõem o programa experimental dessa pesquisa. A partir dos resultados obtidos, constatou-se que as deformações por colapso aumentam com a redução do grau de compactação do solo. A umidade inicial do solo antes da inundação também influencia a magnitude do colapso. Solos com baixas umidades iniciais apresentam maior colapso ao serem umedecidos. Para o solo estudado, deformações por colapso são pequenas e praticamente desprezíveis para solos compactados com grau de compactação mínimo de 90%. Ensaios realizados com amostras compactadas nas mesmas condições de compacidade do solo natural no campo demonstraram que a deformabilidade do solo é afetada por sua baixa densidade e que a magnitude dos colapsos podem ser superiores àquelas obtidas para o mesmo solo em condição natural. No trabalho, uma representação mais prática da relação dos potenciais de colapso com a curva de compactação do solo é proposta. Assim, verificou-se que a compactação deve ser realizada com um controle suficientemente capaz de reduzir os problemas advindos da colapsibilidade dos solos.
Compaction influence on sandy soil collapse
Keywords: Collapsible soil; Compaction; Collapse potential; Suction; Solo colapsível; Compactação; Potencial de colapso; Sucção